2017
DOI: 10.1212/wnl.0000000000003652
|View full text |Cite
|
Sign up to set email alerts
|

Long-term functional outcome in patients with acquired infections after acute spinal cord injury

Abstract: Hospital-acquired Pn/Wi are predictive of propagated disability and mortality after SCI. Pn/Wi qualify as a potent and targetable outcome-modifying factor. Pn/Wi prevention constitutes a viable strategy to protect functional recovery and reduce mortality. Pn/Wi can be considered as rehabilitation confounders in clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
62
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(66 citation statements)
references
References 38 publications
3
62
0
1
Order By: Relevance
“…To the author's knowledge, this is the first work that describes the clinical profile of Covid-19 in a cohort of SCI patients. The vulnerability of people with SCI is well known [5][6][7][8][9][10]. We have found that more than half of our patients showed one or two symptoms at the moment of Covid-19 confirmation, which is lower than the symptomatic expression in other published case series [18].…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…To the author's knowledge, this is the first work that describes the clinical profile of Covid-19 in a cohort of SCI patients. The vulnerability of people with SCI is well known [5][6][7][8][9][10]. We have found that more than half of our patients showed one or two symptoms at the moment of Covid-19 confirmation, which is lower than the symptomatic expression in other published case series [18].…”
Section: Discussionmentioning
confidence: 54%
“…Suppression of the immune system after SCI is due to noradrenergic overactivation and excess glucocorticoid release via hypothalamus-pituitary-adrenal axis stimulation [8] and also to autoimmunity [9]. Both phenomena, respiratory failure and injury-induced immunosuppression, are more pronounced after cervical or high-thoracic compared with low-thoracic SCI level, which explains why pneumonia is the leading cause of mortality in SCI patients [10]. As Covid-19 is a novel viral respiratory infection, its epidemiology and clinical course among people with SCI are yet unknown.…”
Section: Introductionmentioning
confidence: 99%
“…To the author´s knowledge, this is the first work that describes the clinical profile of Covid-19 in a cohort of SCI patients. The vulnerability of people with SCI is well known [6][7][8][9][10][11] . We have found that more than half of our patients showed one or two symptoms at the moment of Covid-19 confirmation, which is lower than the symptomatic expression in other published case series 18 .…”
Section: Discussionmentioning
confidence: 99%
“…2 The aim of this study was to investigate whether infections occurring in an acute care setting after SCI affected long-term functional recovery and survival. 4 METHODS Data source and inclusion criteria. The study by Kopp et al 4 used data gathered from the multicenter National Spinal Cord Injury Database (NSCID).…”
mentioning
confidence: 99%
“…4 METHODS Data source and inclusion criteria. The study by Kopp et al 4 used data gathered from the multicenter National Spinal Cord Injury Database (NSCID). The NSCID prospectively gathers data from 25 specialized traumatic SCI care centers.…”
mentioning
confidence: 99%